2008
DOI: 10.1007/s12311-008-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum: Connections and Functions

Abstract: In addition to its role in motor control, reflex adaptation, and motor learning, three sorts of evidence have been put forward to support the idea that the cerebellum may also be involved in cognition. Patients with cerebellar lesions are reported to have deficits in performing one or another cognitive task. The cerebellum is often seen to be activated when normal subjects perform such tasks. There are connections to and from areas of the prefrontal cortex that may be involved in cognition. In this paper, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 23 publications
(28 reference statements)
3
97
1
2
Order By: Relevance
“…In the latter two cases, recorded cortical neurons fired in advance to the onset of the respective vibrissal or eyelid CRs. From a hodological point of view, selective motorrelated cortical areas seem to project both to the cerebellum and to the facial nucleus as shown with different neuroanatomical and electrophysiological procedures Manvelyan, 1984, 1987;Morcuende et al, 2002;Ramnani et al, 2006;Glickstein and Doron, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter two cases, recorded cortical neurons fired in advance to the onset of the respective vibrissal or eyelid CRs. From a hodological point of view, selective motorrelated cortical areas seem to project both to the cerebellum and to the facial nucleus as shown with different neuroanatomical and electrophysiological procedures Manvelyan, 1984, 1987;Morcuende et al, 2002;Ramnani et al, 2006;Glickstein and Doron, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that the cerebellum is involved in sensory -motor control and learning of motor skills [72,73]. The relative expansion of the cerebellum in primates together with stereopsis and elaboration of the visual system [19,20,68] presumably underpins primates' fine visuo-motor control and manual dexterity.…”
Section: Cognitive Implicationsmentioning
confidence: 99%
“…It has been suggested that eye movements explain much of the cerebellar activity associated with cognitive tasks in neuroimaging experiments and that these areas are connected with the frontal eye fields (Glickstein and Doron 2008). Although the cerebellar cortex does indeed have connections with the frontal eye fields, these are in addition to a number of other prefrontal regions that connect with the cerebellum, but make no known contributions to the kinematics of eye movements.…”
Section: Differences In Processing First-and Second-order Rules In Thmentioning
confidence: 99%